2004
DOI: 10.1038/nm985
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose alleviates polyglutamine-mediated pathology in a mouse model of Huntington disease

Abstract: Inhibition of polyglutamine-induced protein aggregation could provide treatment options for polyglutamine diseases such as Huntington disease. Here we showed through in vitro screening studies that various disaccharides can inhibit polyglutamine-mediated protein aggregation. We also found that various disaccharides reduced polyglutamine aggregates and increased survival in a cellular model of Huntington disease. Oral administration of trehalose, the most effective of these disaccharides, decreased polyglutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
559
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 699 publications
(590 citation statements)
references
References 39 publications
17
559
2
2
Order By: Relevance
“…Trehalose treatment increased the median life span of the naglu –/ – mice by 6.4 weeks ( P  < 0.0001) (Figure 1(a)). Trehalose did not affect the body weight (Figure 1(b)) and did not cause any obvious adverse effects in WT mice, which is consistent with previous reports [34,37,41,42].
10.1080/15548627.2018.1474313-F0001Figure 1.Trehalose treatment increases the life span and reduces hyperactivity and anxiety-related behavior in naglu −/- mice.
…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Trehalose treatment increased the median life span of the naglu –/ – mice by 6.4 weeks ( P  < 0.0001) (Figure 1(a)). Trehalose did not affect the body weight (Figure 1(b)) and did not cause any obvious adverse effects in WT mice, which is consistent with previous reports [34,37,41,42].
10.1080/15548627.2018.1474313-F0001Figure 1.Trehalose treatment increases the life span and reduces hyperactivity and anxiety-related behavior in naglu −/- mice.
…”
Section: Resultssupporting
confidence: 90%
“…Trehalose has peculiar physical-chemical properties that confer chaperone-like activities [42], such as the ability to stabilize mutant proteins [41,42,58]. Moreover, protein aggregates in neurodegenerative diseases are substrates of autophagy [21,36,59,60], a pathway that is enhanced by trehalose [3040].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka et al (2004) have shown that various disaccharides can reduce polyglutamine aggregates and increase survival in an in vitro model of HD by binding to the expanded polyglutamine tails and stabilizing the partially unfolded polyglutamine-containing proteins. Importantly, oral administration of trehalose (the most effective of these disaccharides) starting at 21 days, was also proven to be beneficial in R6/2 mice by decreasing the number of polyglutamine aggregates in their brains, improving their motor dysfunction (as assessed by the rotarod and the footprint tests), and extending their lifespan by 10.14% (Tanaka et al, 2004). To date there has been no demonstration that trehalose crosses the blood brain barrier and therefore the exact mechanism of action of this disaccharide deserves further investigation.…”
Section: 3mentioning
confidence: 99%
“…It is important to note that certain osmolytes can be used to protect proteins from misfolding/aggregation and thereby maintaining/ restoring their intracellular functional activity (42,43), which otherwise may be prone to certain disease conditions. In fact, the utility of osmolytes as potential therapeutic interventions for neurodegenerative diseases, particularly associated with pathological conditions arising due to polyQ chain length extension, has been supported by studies in which osmolyte trehalose has been used as a preventive tool for Huntington's disease in transgenic animal mice (44). Osmolyte trehalose has been reported to activate macroautophagy possibly by the stabilization of the expanded polyQ protein and thereby preventing conversion of the expanded polyQ into aggregation-prone b-sheet-rich conformation (45,46).…”
Section: Naturally Occurring Osmolytes: a Potential Therapeutic Tool mentioning
confidence: 99%